2014
DOI: 10.1007/s10014-014-0192-2
|View full text |Cite
|
Sign up to set email alerts
|

Epithelioid glioblastoma arising from pleomorphic xanthoastrocytoma with the BRAF V600E mutation

Abstract: Pleomorphic xanthoastrocytoma (PXA) is classified by the World Health Organization as a grade II astrocytic tumor with relatively favorable prognosis among gliomas. A valine-to-glutamic acid substitution at position 600 of the serine/threonine-protein kinase BRAF (BRAF V600E) mutation, which is commonly found in PXA, has recently been detected in approximately 50% of all epithelioid glioblastoma (GBM) cases. We herein report a case of epithelioid GBM developing at the site of a left temporal PXA 13 years after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 32 publications
3
83
0
1
Order By: Relevance
“…Furthermore, methylome analysis showed that one of our four tested eGBMs had a methylation pattern that clustered with conventional PXA. Lastly, a case recently reported by Tanaka et al (26) showed an eGBM developing within the tumor bed of a PXA 13 years after initial resection.All these data suggest that eGBM and ePXA are either the same entity or highly related.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, methylome analysis showed that one of our four tested eGBMs had a methylation pattern that clustered with conventional PXA. Lastly, a case recently reported by Tanaka et al (26) showed an eGBM developing within the tumor bed of a PXA 13 years after initial resection.All these data suggest that eGBM and ePXA are either the same entity or highly related.…”
Section: Discussionmentioning
confidence: 92%
“…In our practice, we have occasionally encountered PXAs with anaplastic transformation showing cytologic characteristics that are indistinguishable from those of eGBM. In a similar fashion, a case report of eGBM arising in a PXA has recently been reported (26). As with eGBM, PXAs with anaplastic transformation most often afflict children and young adults, although cases in older patients have also been reported (3,15).…”
Section: Introductionmentioning
confidence: 92%
“…[6] Similarly, Tanaka et al also described a case of Ep-GBM arising in a patient diagnosed with PXA 13-years after the treatment. [7] Considering the above two examples it seems that Ep-GBMs are closely related with PXA which is a low grade glial tumor in comparison to conventional GBMs. However, since Ep-GBM has poor outcomes than typical GBM as well as uncertain response to temozolamide, this hypothesis is questionable and needs further evaluation.…”
Section: Pathological Findingsmentioning
confidence: 95%
“…Пропозиції доповнити класифікацію гліоб-ластом епітеліоїдним варіантом лунали з 1998 року [20], стримувалися відносно незначним від-сотком цих пухлин, але зараз стало відомо, що ця група пухлин демонструє молекулярні зміни, характерні для дитячих форм астроцитом, а саме плеоморфної ксантоастроцитоми (мутація гену BRAF), що дозволяє припустити особливий он-тогенез [21,22].…”
Section: Morphologia • 2016 • том 10 • № 3 • морфологіяunclassified